Immunohistochemical Expression of Ki67 and p53 in Wilms Tumor and Its Relationship with Tumor Histology and Stage at Presentation. (20th January 2016) - Krishna, O. H. Radhika; Kayla, Geetha; Abdul Aleem, Mohammed; Malleboyina, Ramani; Reddy Kota, Ramesh
Abstract : Aim . Evaluate tumor proliferation marker (Ki67) and p53 tumor suppressor marker in Wilms tumor and correlate with histology, anaplasia, and staging. Design . Prospective, hospital based study conducted at a tertiary pediatric referral centre in south India. Setting . Wilms tumor is the most common childhood renal malignancy worldwide. Anaplasia on histology is associated with treatment resistance but not with aggressiveness clinical presentation. Chemotherapy for Wilms tumor is based on histology and staging. Most patients respond to current chemotherapy protocol. However, a small fraction relapses or metastasizes. Affordable prognostic markers are needed for histopathological evaluation of this tumor. Subjects . Cases of histologically confirmed Wilms tumor over five years. Cases after chemotherapy were excluded as the immunostaining was inconsistent in necrotic areas. Methods . The clinical and radiological findings of 31 cases of Wilms tumor were documented at a tertiary pediatric referral hospital over five years. In addition to Hematoxylin and Eosin staining, Ki67 proliferation index and p53 expression were correlated with tumor histology and staging. Results . Age incidence was 3–8 years with female preponderance. Significant correlation was noted between Ki67 proliferation index and tumor staging. p53 expression was not useful in stratification of Wilms tumor. Conclusion . Ki67 was cost-effective immunohistochemical marker for prognostication of pediatric Wilms tumor.